The Effect of Special Exercises On Learning the knuckleball kick Skill According to Speed and Spin of Smart Ball for Youth Football Players - Ibrahim, Ismael; Abd-Ali, Raafat (Journal of Physical Education, 2016)
Recently new technique has been detected in scoring through biomechanics analysis of some of the free kicks from stability. It was the knuckleball kick that has become of great importance in games. Specifically in the scoring from stability as it is difficult for goalkeepers to hold off that kick and it is difficult to predict its path. Moreover, the performance of such as this kick needs to learn the technical performance and perfected through knowledge of the motor trajectory to those skilled. Through practice, the skill will reach perfection in performance. In remained technological advances in hardware and tools used in the sporting side, it was necessary to simulate this development with serve to the game of football. such as smart ball, Through it the development of players in the skill level of stability in the scoring direct free kicks or scoring without the wall as well knuckleball kick by giving an assessment of the performance information, As is the importance of research in learning the knuckleball kick skill according to the variables of speed and spin. The problem of research sets in non-Iraqi players learn the skill of scoring knuckleball kick and in the importance of recognizing speed and spin variables of the ball for this kind of scoring stability.